1985
DOI: 10.1029/jc090ic01p00903
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the mixed layer at OWS November and Papa with several models

Abstract: The Mellor‐Yamada level‐2 and 2 1/2, Niiler, and Garwood one‐dimensional mixed‐layer models were compared for some simple forcing experiments and were tested by simulating changes in the mixed layer at ocean stations November and Papa for the year 1961. The ocean station simulations show that the models can be tuned to give fairly good results. However, the need to readjust model constants when changing locations suggests that there is room for improving some of the mixing parameterizations. The sensitivity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
210
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(231 citation statements)
references
References 35 publications
15
210
0
3
Order By: Relevance
“…Internal waves were not as pronounced in the model as in observations. The simulated mixed layer was too shallow, as was previously shown by Martin [1985] The horizontal resolution of the model (5 km) was only sufficient for a description of large-scale circulation patterns (which happens to be of the most interest to LMMBS). The point-to-point comparison of mean currents was most successful in the southern basin, which is characterized by a relatively smooth bathymetry.…”
Section: Currentsmentioning
confidence: 93%
See 1 more Smart Citation
“…Internal waves were not as pronounced in the model as in observations. The simulated mixed layer was too shallow, as was previously shown by Martin [1985] The horizontal resolution of the model (5 km) was only sufficient for a description of large-scale circulation patterns (which happens to be of the most interest to LMMBS). The point-to-point comparison of mean currents was most successful in the southern basin, which is characterized by a relatively smooth bathymetry.…”
Section: Currentsmentioning
confidence: 93%
“…We present some of the more comprehensive current meter records here, while the complete model/observation comparison is given by Schwab and Beletsky [1998]. [Martin, 1985]. In addition, the modeled thermocline is too diffuse.…”
Section: Comparison With Observationsmentioning
confidence: 99%
“…It also indirectly affects the mixed layer depth (MLD) by altering the vertical turbulent mixing in the upper water column [e.g., Lewis et al, 1990]. The positive buoyancy forcing generated by this subsurface heating is primarily responsible for stabilizing the surface waters [e.g., Martin, 1985], which in turn contributes to the formation of the upper ocean thermocline.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Jones and Monismith (2008) and Carniel et al (2009) suggested suitable choices of β032000 and β056000, respectively. Zhang et al (2011a) obtained β≈4×10 5 through assimilating OWS Papa dataset of Martin (1985) in summer into a 1-D numerical model, in which wave breaking was considered, for estimating β via a variational approach. The value is two times larger than the one suggested by Mellor and Blumberg (2004).…”
Section: Experiments Designmentioning
confidence: 99%